University proceedings. Volga region. Social sciences - V.G. Romanovskiy (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. The development of digital technologies has led to the emergence of a new type of crime – digital, which in the broadest sense of the word is understood as a set of crimes committed in cyberspace with the help of digital technologies. At the same time, additional terms are used – cybercrime, high-tech crime, which in most studies are considered synonymous. This contributes to the emergence of a new section – digital crim-inology, which largely overcomes the established conservative principles of analysis of modern crime. These circumstances update research on digital crime. The presented theses and proposals can be used both in Russian legal science and in the practice of investigating crimes committed in cyberspace. The purpose of the study is to conduct a study of the con-cept of digital crime; highlight its features; systematize the main features proposed in both domestic and foreign doctrine; identify the key problems of combating crimes in cyber-space. Materials and methods. Research problems were solved through scientific analysis of a wide range of sources on key aspects of digital crime. As a research method, first of all, a comparative legal one was used, which made it possible to explore the concept of digital crime and compare it with similar terms used by foreign law enforcement agencies (USA, UK, People's Republic of China). Methods of legal statistics were used, thanks to which trends in the development of cybercrime are identified. Results. The general concept of dig-ital crime is presented, its influence on modern criminological science is shown. Conclu-sions. The article formulates general conclusions about the continued trend of expanding digital crime, the emergence of new subjects of criminal law (Artificial intelligence, an-thropoid robots), the development of digital criminology, and the transformation of the principles of criminal law.